Inside the NBA Bubble: How Black Players Performed Better without Fans - Mauro Caselli; Paolo Falco; Babak Somekh (Global Labor Organization (GLO), 2022)
In the NBA, predominantly Black players play in front of predominantly non-Black fans. Using the 'NBA bubble', a natural experiment induced by COVID-19, we show that the performance of Black players improved significantly with the absence of fans vis-à-vis White players. This is consistent with Black athletes being negatively affected by racist pressure from mostly non-Black audiences. We dispel several alternative hypotheses. Beyond hurting individual players, fans' behavior causes significant economic damage to the NBA by lowering the quality of the game.
Keywords: D91; J15; J71; Z22; 330; discrimination; harassment; racism; performance; basketball; NBA; COVID-19